Daun Timbul dalam Ekspresi Karya Seni Rupa - Sumarjaya Putra, I Made Adi; Sujana, I Wayan; Supriyatini, Sri (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2022)
This MBKM Independent Project report, bearing the title